An institution-based view of ownership in cross-border acquisitions: mimetism by Latin American firms - Pinto, Cláudia Sofia Frias (2017)
This study draws upon the institution-based view to explain the ownership decisions by Latin American multinationals (LAMNCs) in cross-border acquisitions (CBAs). We specifically examine (1) the effect of institutional distance on the ownership acquired, (2) the mimicking behaviors regarding ownership of MNCs from Latin American countries when undertaking CBAs and (3) if acquiring a related business impact the strength of institutional distance and mimetic isomorphism. We endeavor into investigating four levels of imitation sources, including firms own prior experience, home and foreign firms, and industry competitors. The results of the empirical tests, using a logistic regression analysis on a sample of 1,334 CBAs by LAMNCs and a cross-sectional sample of 567 CBAs from the manufacturing industry, over a 20-year period (1995-2015), support an institutional-based framework with different influences in the ownership choices in CBAs. Our findings provide evidence that MNCs prefer to acquire full ownership when investing in institutionally distant countries. Furthermore, we confirmed that the mimicking behavior of MNCs pertaining to ownership in CBAs occurs at four levels. Finally, the influence of institutional distance, mimicking of foreign fims and industry competitors are strengthened by the acquisition of a related business, albeit the effect of mimicking own firm prior experiences and home firms is weakened by the acquisition of a related business. We contribute to the institution-based view of international strategy identifying the specific mimetic behaviors of firms’ internationalization ownership in foreign operations. Moreover, we also contribute to the burgeoning literature on LAMNCs, or multilatinas, by providing a better understanding of their strategies regarding CBAs. We use a multi level approach to bring a new understanding of how LAMNCs mimic ownership decisions in CBAs. To the study on ownership, and specifically ownership in CBAs, we contribute for a behavioral interpretation and consider isomorphism between MNCs, going beyond conventional determinants such as transaction costs, informational asymmetry or uncertainty.